SOVEREIGN BONDS AND ITS RELATIONSHIP WITH GLOBAL SCENE OF MACROECONOMIC - Gomero Gonzales, Nicko Alberto (2014)
The Government or sovereign bonds are configuring as an important source of funding for the Peruvian government. Capital needs to finance its budgetary imbalances and solve their investment projects are be-ing leveraged in the stock market, a situation that will result in lower financial costs and also, a greater deepe-ning and inclusiveness of this market. Macroeconomic strengths are conducive to issue these documents, given the benefits of this title, the oversubscription involve the government to monitor for issues made. The stability of the home front is reflected in the beha-vior tendency of TIR sovereign bonds, a fact that was also evident in the other securities issued by the major economies of the world, whose reading tells us that the global economy has come back to path of growth.